Rubric for assessing ICT infrastructure in Malaysia Higher Education - Mokhtar, Shamsul Anuar; Alias, Rose Alinda; Abdul Rahman, Azizah (2006)
Access to ICT infrastructure is a key determinant of a higher education institution’s ability to deliver teaching and learning effectively. The paper proposes a rubric for assessing ICT infrastructure with regards to the implementation of academic computing in Malaysian higher education institutions. Based on a selection of seven survey questionnaires and rubrics that are used to assess ICT implementation, the paper identifies thirteen performance indicators grouped into four distinct ICT components. The ICT components are computers, network and Internet, display screen technologies and peripherals, and software and information systems. The availability of computers is assessed based on computers to students, Internet-enabled computers to students, computers to academic staff and Internet-enabled computers to academic staff ratios. The performance indicators for network and Internet include network specification, Internet bandwidth, wireless coverage and network/Internet performance. Display screen technologies and peripherals cover percentage of classrooms equipped with display screen technologies and types of computer peripherals. Software and information systems encompass performance indicators related to the availability of application software, learning platforms and academic/student information systems. The paper then uses these performance indicators to describe the characteristics of three case higher education institutions representing low, moderate and high level of ICT implementation. The combination of these performance indicators and description of characteristics form the ICT infrastructure assessment rubric.